Seasonal Patterns of Body Temperature Daily Rhythms in Group-Living Cape Ground Squirrels Xerus inauris - Scantlebury, M.; Danek-Gontard, M.; Bateman, Bill; Bennett, N.; Manjerovic, M.; Joubert, K.; Waterman, J. (Public Library of Science, 2012)
Organisms respond to cyclical environmental conditions by entraining their endogenous biological rhythms. Suchphysiological responses are expected to be substantial for species inhabiting arid environments which incur large variationsin daily and seasonal ambient temperature (Ta). We measured core body temperature (Tb) daily rhythms of Cape groundsquirrels Xerus inauris inhabiting an area of Kalahari grassland for six months from the Austral winter through to thesummer. Squirrels inhabited two different areas: an exposed flood plain and a nearby wooded, shady area, and occurred indifferent social group sizes, defined by the number of individuals that shared a sleeping burrow. Of a suite of environmentalvariables measured, maximal daily Ta provided the greatest explanatory power for mean Tb whereas sunrise had greatestpower for Tb acrophase. There were significant changes in mean Tb and Tb acrophase over time with mean Tb increasingand Tb acrophase becoming earlier as the season progressed. Squirrels also emerged from their burrows earlier andreturned to them later over the measurement period. Greater increases in Tb, sometimes in excess of 5uC, were noted duringthe first hour post emergence, after which Tb remained relatively constant. This is consistent with observations that squirrelsentered their burrows during the day to ‘offload’ heat. In addition, greater Tb amplitude values were noted in individualsinhabiting the flood plain compared with the woodland suggesting that squirrels dealt with increased environmentalvariability by attempting to reduce their Ta-Tb gradient. Finally, there were significant effects of age and group size on Tbwith a lower and less variable Tb in younger individuals and those from larger group sizes. These data indicate that Capeground squirrels have a labile Tb which is sensitive to a number of abiotic and biotic factors and which enables them to beactive in a harsh and variable environment.